Communication for International Careers 1 - POP-FLANJA, Delia (2021)
The general objective of the course Communication for InternationalCareers 1 is to acquaint students with professional elements pertaining towritten and oral communication in English, for the purpose of offeringthem the skills necessary to develop international careers. Some of the mostimportant specific objectives are to develop the range of vocabularyutilized by students in the process of communicating, to increase students’adaptability to a wide range of communication situations and to developpractical abilities which are needed to participate in complexcommunication situations.